Exploring the role of different coping styles in mediating the relationship between dyadic adjustment status and postpartum depression among postnatal women: a single-centre, cross-sectional study - Jing Chen; Jing Deng; Fan Liu; Xiujing Guo; Yifei Tan (BMJ Open)
Objectives Postpartum depression (PPD) is a prevalent complication of childbearing, with numerous risk factors associated with its onset. Although the risk factors for PPD among postpartum women have been studied, the mechanisms underlying these factors remain inadequately understood. This study aimed to investigate the direct and mediating roles of different coping styles in the relationship between dyadic adjustment status and PPD among women 6 weeks postdelivery.Design Single-centre, cross-sectional study.Setting A tertiary care setting in Chengdu City, Sichuan Province, China, from July 2022 to January 2023.Participants The study involved 626 women 6 weeks post-delivery.Outcome measures The Dyadic Adjustment Scale, the Simplified Coping Style Questionnaire and the Edinburgh Postnatal Depression Scale (EPDS) were used to evaluate the dyadic adjustment status, coping styles and the depressive condition of postpartum women, respectively. Data analysis encompassed correlation and mediation analyses based on structural equation modelling.Results EPDS scores were significantly correlated with all four dimensions of dyadic adjustments status as well as with both positive and negative coping styles. Dyadic consensus (β = −0.16, p=0.005), affectional expression (β = −0.14, p=0.008) and dyadic cohesion (β = −0.10, p=0.037) directly correlated with PPD after adjusting for covariates. For dyadic satisfaction, the mediating effects of positive and negative coping styles on PPD were −0.04 (95% CI: −0.08 to –0.01) and −0.07 (95% CI: −0.11 to –0.03), respectively. Moreover, both positive and negative coping styles were identified as mediators in the relationship between dyadic cohesion and PPD, with mediating effects of −0.01 (95% CI: −0.03 to –0.00) and −0.09 (95% CI: −0.14 to –0.04), respectively. No mediation was found in the association between affectional expression and PPD.Conclusion Our findings suggest that both positive and negative coping styles mediate the relationship between dyadic adjustment status and PPD, especially concerning dyadic satisfaction and dyadic cohesion.